Enzymatic Bioremediation: Current Status, Challenges of Obtaining Process, and Applications - Okino-Delgado, Clarissa Hamaio [UNESP]; Zanutto-Elgui, Mirella Rossitto [UNESP]; do Prado, Débora Zanoni [UNESP]; Pereira, Milene Stefani [UNESP]; Fleuri, Luciana Francisco [UNESP] (Springer Nature, 2019)
Enzymes play an important role for degradation of various xenobiotic compounds. In this chapter, we summarize the role of various enzymes including oxidoreductases, monooxygenases, dioxygenases, peroxidases, and laccases for bioremediation of various xenobiotic compounds. Microbial oxidoreductases are able to degrade natural and artificial pollutants, reverse toxicity caused by xenobiotics, and reduce heavy metals, through their oxi-reduction capacity. Monooxygenases and dioxygenases are able to play a central role in the degradation and detoxification of aromatic compounds through hydroxylation and ring cleavage. Peroxidases act in bioremediation processes due to their thermostability and capacity to oxidize a wide range of substrates. Laccases can act on a variety of pollutants including petroleum derivatives (PHAs), paints, plastics, dyes, estrogenic substances, and paper via oxidative reactions, decarboxylation, and demethylation and can oxidize phenols, polyphenols, metals, polyamines, and aryl diamines groups and also act on lignin degradation and on azo dyes.
Keywords: Dioxygenase; Laccases; Monooxygenase; Peroxidase